2022
DOI: 10.18502/ijph.v51i5.9426
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Behaviors and Associated Factors among Iranian Adult Population: A National Survey

Abstract: Background: There is no official and representative information on certain health-risk behaviors in Iran. This national survey was performed to determine the prevalence of five high-risk behaviors among the adult population and underlying factors. Methods: This cross-sectional study was performed in 23 provinces of Iran in 2019 involving 10,957 participants. The following five risky behaviors were evaluated: (a) using illicit drugs in the past month, (b) drinking alcohol in the past month, (c) having ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Four studies used mixed-methods designs, utilizing surveys and interviews, to explore how the built environment was linked to physician satisfaction (Folscher et al, 2015; Pleban et al, 2021; Silva et al, 2021; Waroonkun, 2020). Two studies used cross-sectional comparison design to compare well-being across two different built environments (Brambilla et al, 2020; Sen et al, 2018), and seven used cross-sectional correlations to evaluate the relationship between exposure to various built environment elements and well-being (Jalili et al, 2013; Lin et al, 2013; Lupo et al, 2021; Marques et al, 2018; Raffier-Peres & Estryn-Behar, 2015; Ratnapalan et al, 2011; Wu et al, 2008). One study used a longitudinal mixed-methods design with surveys and interviews, in which the evaluations were conducted before and after moving to a newly constructed hospital unit (Rice et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies used mixed-methods designs, utilizing surveys and interviews, to explore how the built environment was linked to physician satisfaction (Folscher et al, 2015; Pleban et al, 2021; Silva et al, 2021; Waroonkun, 2020). Two studies used cross-sectional comparison design to compare well-being across two different built environments (Brambilla et al, 2020; Sen et al, 2018), and seven used cross-sectional correlations to evaluate the relationship between exposure to various built environment elements and well-being (Jalili et al, 2013; Lin et al, 2013; Lupo et al, 2021; Marques et al, 2018; Raffier-Peres & Estryn-Behar, 2015; Ratnapalan et al, 2011; Wu et al, 2008). One study used a longitudinal mixed-methods design with surveys and interviews, in which the evaluations were conducted before and after moving to a newly constructed hospital unit (Rice et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Of the sixteen studies that met the inclusion criteria, all had been found in peer-reviewed journals. Nine were conducted in Europe (Björndell & Premberg, 2021; Brambilla et al, 2020; Rice et al, 2008; Lupo et al, 2021; Pleban et al, 2021; Raffier-Peres & Estryn-Behar, 2015; Ratnapalan et al, 2011; Sen et al, 2018; Silva et al, 2021), three in East Asia (Lin et al, 2013; Waroonkun, 2020; Wu et al, 2008), two in the Middle East (Jalili et al, 2013; Kebapcı & Güner, 2021) and one each in Brazil (Marques et al, 2018) and South Africa (Folscher et al, 2015). Notably, none of the studies that met the inclusion criteria had been conducted in the United States, indicating a significant gap in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations